Role of oral hypoglycaemic drugs in preventing complication in non-alcoholic fatty liver disease with type 2 diabetes mellitus - Zahid, Museera; Perwaiz Khan, Samia; Ershad, Sana; Izhar, Safia; Warraich, Rizwana; Asghar, Ali (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the prevalence of non-alcoholic fatty liver disease, and the effect of oral hypoglycaemic drugs and lifestyle modifications in reducing fatty liver changes and liver enzymes in these patients. Method: The comparative, observational study was conducted at the Department of Pharmacology, Sohail University, Karachi, from October 2022 to October 2023, and comprised patients of either gender having elevated liver enzymes and ultrasound finding of fatty liver changes along with raised glycated haemoglobin, transaminases, total cholesterol and triglycerides. The participants were prescribed oral hypoglycemic agents by endocrinologists. Those given empaglifazolin + metformin were in group A, empaglifazolin + linglaptin in group B, sitaglaptin + metformin in group C, metformin alone in group D and sitaglaptin alone in group E. Lifestyle modifications were advised in all the treatment groups, while control group F was only advised lifestyle modifications. The intervention lasted 3 months. Investigations included B-mode ultrasound liver, liver enzymes and glycated haemoglobin, which were done at baseline and after the intervention. Data was analysed using SPSS 25. Result: Of 200 patients, 40 were males and 160 were females in ratio of 1:4. The overall mean age was 48+16 years. There were 154(77%) patients who had non-alcoholic fatty liver disease with type 2 diabetes mellitus, while 46(23%) had only fatty liver changes. There were 50(25%) patients in group A, 30(15%) in group B, 30(15%) in group C, 40(20%) in group D, 10(5%) in group E, and 40(20%) in group F. Post-intervention improvement was noted in 48(24%) patients, with 20(41.7%) of them being in group A. Conclusion: The prevalence of non-alcoholic fatty liver disease with type 2 diabetes was high. Combination of empagliflozin + metformin along with lifestyle modifications was highly effective in reducing fatty changes and the level of liver enzymes. Key Words: Non-alcoholic fatty liver diseases, Metformin, SGLT2- inhibitor, Type 2 diabetes mellitus, AST, ALT.